2018
DOI: 10.3390/nu10101500
|View full text |Cite
|
Sign up to set email alerts
|

Improved Diet Quality and Nutrient Adequacy in Children and Adolescents with Abdominal Obesity after a Lifestyle Intervention

Abstract: High rates of childhood obesity require integral treatment with lifestyle modifications that achieve weight loss. We evaluated a lifestyle intervention on nutrient adequacy and diet quality in children and adolescents with abdominal obesity. A randomized controlled trial was performed on 107 participants, assigned either to a usual care group or to an intensive care group that followed a moderate hypocaloric Mediterranean diet and received nutritional education. Intake adequacy was evaluated using Dietary Refe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
121
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(133 citation statements)
references
References 56 publications
7
121
0
5
Order By: Relevance
“…Our lifestyle intervention achieved a significant reduction in adiposity (higher than 0.25) which could reduce cardiovascular risk. In addition, we observed a greater improvement in diet quality and physical activity levels in those participants enrolled in the intervention group as has been the case in other intervention studies 27,47‐49 …”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our lifestyle intervention achieved a significant reduction in adiposity (higher than 0.25) which could reduce cardiovascular risk. In addition, we observed a greater improvement in diet quality and physical activity levels in those participants enrolled in the intervention group as has been the case in other intervention studies 27,47‐49 …”
Section: Discussionsupporting
confidence: 83%
“…In contrast, the intervention group was given a moderately hypocaloric Mediterranean diet, based on a fixed full‐day meal plan 27 . Their energy expenditure was calculated using Schofield equation (adapted to age and sex) 28 .…”
Section: Methodsmentioning
confidence: 99%
“…The differences between the group of obese and children with normal weight amounted an average of 1000 kcal, which is 30% more calories than they required, taking into consideration their proper weight age and gender. The results of other studies also show an excess of energy in the diets of obese children [12][13][14]. The analysis of the individual components being the source of the energy excess in [12,15].…”
Section: Discussionmentioning
confidence: 92%
“…The analysis of the individual components being the source of the energy excess in [12,15]. What is interesting, also in the population of obese children from Spain it was observed that, respectively, 45% and 38% of the studied obese children had fat and carbohydrate intake levels above the norms (Acceptable Macronutrient Distribution Range-AMDR) [14]. Similar results were observed in overweight Greek children, who consumed less energy from carbohydrates and more from fat, ac-cording to AMDR [15][16][17].…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, no changes in the overall energy intake were anticipated prior to study commencement. Also, according to international standards (58), it is inappropriate to reduce the energy intake in adolescents. Therefore, the focus is how to correct the pattern of food consumption.…”
Section: Discussionmentioning
confidence: 99%